Agent of Bicultural Balance: Ganma, Yothu Yindi and the Legacy of Yunupinu - Corn, Aaron (Journal of World Popular Music, 2014)
This article demonstrates how the remote ganma “converging currents” site on the Gumatj Yolnu homeland of Biranybirany in Arnhem Land has influenced the course of race relations in Australia through the bicultural agency of one of Australia’s most eminent Indigenous figures: the late Gumatj educator and musician, Mandawuy Yunupinu. It focuses on Yunupinu’s development of ganma as a pedagogical framework through his formative work as a teacher in Yolnu schools in the 1980s, and his parallel incorporation of these ideas into his music for the acclaimed popular band, Yothu Yindi. It will discuss how, through these processes, Yunupinu adapted ganma into a nomothetic paradigm for engendering balance and mutual respect in bicultural exchanges, and how, through his work as the lead singer and composer of Yothu Yindi, this ethos would have a pivotal role in educating the Australian public about its moral and political responsibilities to Indigenous Australians in accessible and inclusive ways. It concludes with an exploration of how Yunupinu’s ganma ethos has influenced Australian ethnomusicologists to work collaboratively with Indigenous communities towards mutually beneficial outcomes, and stands as a testament to his prolific role as a quintessentially Australian “agent of bicultural balance”.